FEATURES OF LONG-TERM MECHANICAL CIRCULATORY SUPPORT WITH CONTINUOUS-FLOW PUMP - G. P. Itkin; E. G. Shokhina; S. Y. Shemakin; V. N. Poptsov; D. V. Shumakov; S. V. Gautier (Вестник трансплантологии и искусственных органов, 2012)
In a review of the comparative analysis of methods and tools for long-term mechanical circulatory support with continuous flow and pulsatile flow implantable pumps. Particular attention is paid to the choice of the optimal modes of the operation of pumps based on the physical principles of the interaction between a the steady flow of blood to the pulsatile mechanics of the heart chambers.